FROM CHAOS TO CLARITY: USING DIGITAL TOOLS, HEURISTIC METHODS, AND PROCESS SIMPLIFICATION TO IMPROVE EFFICIENCY IN LANDSCAPING AND OUTDOOR SERVICES - Yatsiuk, Volodymyr (European Journal of Interdisciplinary Issues, 2025)
Service organizations involved in landscaping and outdoor services have to function in an environment of uncertainty and variability, with factors like demand, which is subject to many variations (i.e., seasonal, daily), weather affects what can be done, employees are mobile and may be in various geographic locations, and all of these factors contribute to an inefficient service operation. Because of this, the workflows associated with these types of organizations are typically disjointed, and most decision-making tends to be reactive rather than proactive. Although digital technology has been implemented at a high rate across service industries, the use of technology alone does not ensure clarity in operation or improvements in performance. The purpose of this paper is to explore how the integration of three concepts: digital tools, heuristic decision-making methods and process simplification can provide for improved operational efficiencies for landscaping and outdoor service organizations. A qualitative approach was used through literature synthesis in order to compile knowledge from studies related to digital transformation, service operations, decision making, and process optimization, in order to create a conceptual model of process and decision making for field-based service organizations. It has been named The Yatsiuk Operational Clarity Framework. The results suggest that operational clarity will exist when digital tools are used in conjunction with simplified workflows and explicit decision rules that enable timely and contextual decisions for managers. The paper provides a practical application of current research related to digital transformation and its relationship to the operational challenges of landscaping and outdoor service organizations.